SURVEI MANAJEMEN PROGRAM EKTRAKURIKULER OLAHRAGA DI SMA SEBAGAI FAKTOR PENDUKUNG OLAHRAGA PRESTASI DI KABUPATAN KLATEN - Nurhadi Santoso; Aris Fajar Pambudi (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2016)
AbstractThis research is motivated by the lack of management on activities in extracurricular organized by schools in KlatenRegency in order to develop the talents of the students. The research aims at fnding out how excellent the levelof management on ektrakurikuler program of sport achievement in SMA Negeri (State Senior High School) thatexist in Klaten Regency is. The instrument used in this study was by using questionnaire. This type of researchwas descriptive research. The subjects of the research were State Senior High Schools that are located in Klatenregency consisting of 15 teachers in charge of sport extracurricular activities. The data analysis techniwue was doneby percentage. The result of data analysis of the research that had been done on the survey of sport extracurricularprogram management in SMA as supporting factor of sport achievement in Klaten Regency is as follows: the excellentmanagement category is 2 schools (13.33%), the good management category is 1 school (6.67%), The mediummanagement category is 7 schools (46.67%), the less management category is 5 schools (33.33%), and the veryless management category is 0 school (0.00%).AbstrakPenelitian ini dilatarbelakangi oleh kurangnya manajemen kegiatan di ekstrakurikuler yang diselenggarakan olehsekolah-sekolah di Kabupaten Klaten dalam rangka mengembangkan bakat peserta didik. Penelitian ini bertujuanuntuk mengetahui seberapa baik tingkat manajemen program ektrakurikuler olahraga prestasi di SMA Negeri yangada di Kabupaten Klaten.Intrumen yang digunakan dalam penelitian ini menggunakan angket. Jenis penelitian iniadalah penelitian deskriptif. Subjek dalam penelitian ini yaitu SMA Negeri yang ada di Kabupaten Klaten sebanyak15 guru penanggung jawab kegiatan ektrakurikuler olahraga. Teknik analisis data dengan persentase. Hasil analisisdata yang telah dilakukan tentang survei manajemen program ekstrakurikuler olahraga di SMA sebagai faktorpendukung olahraga prestasi di Kabupaten Klaten sebagai berikut: kategori manajemen sangat baik sebanyak 2sekolah (13,33%), kategori manajemen baik 1 sekolah (6,67 %), kategori manajemen sedang sebanyak 7 sekolah(46,67 %), kategori manajemen kurang sebanyak 5 sekolah (33,33 %), dan kategori manajemen sangat kurangsebanyak 0 sekolah (0,00 %).